2016
DOI: 10.1128/jvi.02253-15
|View full text |Cite
|
Sign up to set email alerts
|

A Structurally Unresolved Head Segment of Defined Length Favors Proper Measles Virus Hemagglutinin Tetramerization and Efficient Membrane Fusion Triggering

Abstract: Paramyxoviruses include several insidious and ubiquitous pathogens of humans and animals, with measles virus (MeV) being a prominent one. The MeV membrane fusion apparatus consists of a receptor binding protein (hemagglutinin [H]) tetramer and a fusion (F) protein trimer. Four globular MeV H heads are connected to a tetrameric stalk through flexible linkers. We sought here to characterize the function of a 17-residue H-head segment proximal to the stalk that was unresolved in all five MeV Hhead crystal or cocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
(72 reference statements)
0
20
0
Order By: Relevance
“…Four blue hexameric heads represent the six-bladed ␤-propellers of the receptor-binding domains. The heads are connected to the stalk by flexible dimeric linkers (green/blue) and four monomeric connectors (purple) (133,134). The MeV F trimer ectodomain structure (PDB code 5YXW) (154) is shown on the right with monomers represented as blue, purple, and orange.…”
Section: Receptors Tropism and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Four blue hexameric heads represent the six-bladed ␤-propellers of the receptor-binding domains. The heads are connected to the stalk by flexible dimeric linkers (green/blue) and four monomeric connectors (purple) (133,134). The MeV F trimer ectodomain structure (PDB code 5YXW) (154) is shown on the right with monomers represented as blue, purple, and orange.…”
Section: Receptors Tropism and Pathogenesismentioning
confidence: 99%
“…The hydrophobic hinge maintains the H-protein in an autorepressed state prior to receptor binding (134). The head connectors govern proper H-protein tetramerization (133). According to the model, membranebound receptors pull on the heads (Fig.…”
Section: Membrane Fusion Mechanismsmentioning
confidence: 99%
“…1A). Based on our current model of membrane fusion triggering, this region may require structural flexibility to enable receptor binding-induced conformational changes of H, leading to F activation and ensuing fusion pore formation (27,33).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, while the structure of the entire H-stalk linker module (aa 140 to 154) remains to be determined, the first part of the following MeV H connector domain was successfully crystalized and was shown to contain a short ␣-helix (H1) contacting the head domain (aa 155 to 166). Interestingly, the length of the following C-terminal unresolved segment (aa 167 to 183) was recently hypothesized to be crucial for the generation of productive H proteins by controlling proper tetrameric oligomerization (33). The most recent model of membrane fusion triggering indicates that CDV/MeV H-stalk, connector, and head domains fold into native structures that enable intracellular assembly of H/F complexes while temporarily inhibiting the constitutive F-protein activation domain in the central stalk region (referred to as the autorepressed state).…”
mentioning
confidence: 99%
“…The forces responsible for coupling receptor binding by the head to F activation by the stalk have not been elucidated. However, recent work by Navaratnarajah et al (83) has indicated that the rigidity and length and of the measles H head-stalk linker segment influence H tetramerization and fusion promotion.…”
Section: Discussionmentioning
confidence: 99%